2020
DOI: 10.3390/ijerph17124452
|View full text |Cite
|
Sign up to set email alerts
|

Phase Angle as a Marker of Muscular Strength in Breast Cancer Survivors

Abstract: Background: accurate prognostic tools are relevant for decision-making in cancer care. Objective measures, such as bioelectrical impedance (BI), have the potential to improve prognostic accuracy for these patients. This cross-sectional study aimed to investigate whether phase angle (PhA) derived from the electrical properties of the body tissues is a predictor of muscular strength in breast cancer survivors (BCS). Methods: a total of 41 BCS (age 54.6 ± 9.2 years) were evaluated. PhA, obtained at frequency 50 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…The present study aimed at assessing the usefulness of proposed phase angle cutoff, as a marker of bioelectrical impedance analysis (BIA) assessed health-status, and functional capacity in breast cancer (BC) survivors. Retrospective observational data on the studied topic has been considered scarce in the studied population (8,28).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study aimed at assessing the usefulness of proposed phase angle cutoff, as a marker of bioelectrical impedance analysis (BIA) assessed health-status, and functional capacity in breast cancer (BC) survivors. Retrospective observational data on the studied topic has been considered scarce in the studied population (8,28).…”
Section: Discussionmentioning
confidence: 99%
“…BIA analysis is an easy-to-use, non-invasive method that measures the electrical properties of the patient's tissues and has been used for many years to assess body composition including fat-free mass [6,8,9]. Previous studies have found that patients with a high fat-free mass index (FFMI) (calculated from fat-free mass/weight) had a significantly better prognosis than did patients with a low FFMI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations